Biotic resistance in freshwater fish communities: species richness, saturation or species identity?. Issue 8 (4th December 2014) - Henriksson, Anna; Yu, Jun; Wardle, David A.; Englund, Göran
<x xml:space="preserve">Abstract</x> Some communities are susceptible to invasions and some are not. Why? Elton suggested in 1958 that the ability of the community to withstand invading species – its biotic resistance – depends on the number of resident species. Later contributors have emphasized the habitat's ability to support species, as well as the contribution of individual species to the resistance. In this study we use information from 184 introductions of Arctic char into Swedish lakes to study both abiotic and biotic aspects of the resident community's ability to resist introductions. We find that the best model included the proportion of forest cover and the proportion of agricultural land cover in the watershed in combination with the presence versus absence of northern pike. Thus, the most important biotic factor to explain the outcome of introductions of Arctic char is the presence of northern pike, a large piscivore. This means that one single species explains the outcome of the introductions better than does the species richness or the saturation level of the community.